Agricultural Research Center-Hays, Roundup (Kansas Agricultural Experiment Station Research Reports, 2018)
Roundup is the major beef cattle education and outreach event sponsored by the Agricultural Research Center–Hays. The 2018 program is the 104th staging of Roundup. The purpose is to communicate timely, applicable research information to producers and extension personnel. The research program of the Agricultural Research Center–Hays is dedicated to serving the people of Kansas by developing new knowledge and technology to stabilize and sustain long-term production of food and fiber in a manner consistent with conservation of natural resources, protection of the environment, and assurance of food safety. Primary emphasis is on production efficiency through optimization of inputs in order to increase profit margins for producers in the long term.
Keywords: beef cattle